Carbon mineralization dynamics of organic materials and their usage in the restoration of degraded tropical tea-growing soil - Liyanage, Mahesh; Sulaiman, Muhammad Firdaus; Ismail, Roslan; Gunaratne, Gamini Perera; Dharmakeerthi, Randombage Saman; Neranjani Rupasinghe, Minninga Geethika; Mayakaduwa, Amoda Priyangi; Musa, Mohamed Hanafi (Multidisciplinary Digital Publishing Institute, 2021)
Understanding carbon mineralization dynamics of organic amendments is essential to restore degraded lands. This study focused on the restoration potentials of tea-growing soils using organic materials available in tea ecosystems. The Selangor-Briah soil series association (Typic Endoaquepts) consisted of a high- (soil A) and a low-carbon (soil B) soils were incubated with different organic materials and released carbon dioxide (CO2) measured. Two kinetic models were applied to depict the mineralization process. Soil health parameters including microbial biomass carbon and nitrogen, dehydrogenase and catalase activities were determined to assess the restoration potentials. The parallel first-order kinetic model fitted well for all amendments. Gliricidia markedly enhanced the net cumulative CO2 flux in both soils. Charged biochar, tea waste and Gliricidia improved the microbial biomass carbon by 79–84% in soil A and 82–93% in soil B, respectively. Microbial quotients and biomass nitrogen were increased over 50 and 70% in amended soils, respectively. Dehydrogenase activity was significantly accelerated over 80% by compost, charged biochar and tea waste. Charged biochar remarkably increased the soil catalase activity by 141%. Microbial biomass, dehydrogenase and catalase activities, and cumulative CO2 flux were positively correlated (r > 0.452) with one another. The studied amendments showed greater potential in improving the soil quality, while charged biochar, raw biochar and compost enrich the soil recalcitrant C pool ensuring the soil health in long term. Even though biochar sequesters carbon, it has to be charged with nutrients to achieve the soil restoration goals.